A new method for tracing the facial nerve trunk using the posterior auricular nerve. Issue 3 (5th February 2019) - Blau, Ilan; Vaisbuch, Yona; Marom, Assaf
Abstract : Tracing the facial nerve trunk is an essential action in parotid surgery, because of the implications of injury to the nerve or its branches. More than a few landmarks that may help the surgeon in this task have been proposed (e.g., the posterior belly of the digastric muscle, the tragal pointer, among others), under the assumption that additional access methods improve the surgical technique and reduce the possibility of harmful post‐operative consequences. Here we present evidence that the posterior auricular nerve may be used to trace the facial nerve trunk. We dissected 75 cadaveric heminecks, exposed the auricularis posterior muscle and adnexa, and attempted to follow the posterior auricular nerve to the facial nerve trunk. The auricularis posterior muscle, nerve, and artery were identified in all heminecks, securing an anatomically reliable route to the facial nerve trunk. Average length of the nerve from the auricularis posterior muscle to the facial nerve trunk was 28 mm (±6.2 mm). The angle between the posterior auricular nerve and the vertical segment of the FN trunk was 39.5° (±7.7°). We conclude that the posterior auricular nerve may be used as a landmark to trace the facial nerve trunk. It is advantageous due to the relatively simple and consistent regional anatomy, and also because manipulation of this nerve does not present a risk given that the auricularis posterior muscle is vestigial. The proposed landmark is particularly important in revision surgery, where the pre‐auricular anatomy may have been distorted and scarred by previous operations. Clin. Anat. 32:453–457, 2019. © 2019 Wiley Periodicals, Inc.